Studi Komparasi Ketentuan Nafkah Suami Dan Istri Dalam Regulasi Perkawinan Di Indonesia, Brunei Darussalam Dan Tunisia - Yani, Rindi; Izzuddin, Ahmad; Rouf, Abd (Maqasid: Jurnal Studi Hukum Islam, 2025)
The legal provisions regarding alimony between husband and wife as stipulated in the laws and regulations of Indonesia, Brunei Darussalam, and Tunisia represent a spectrum of different approaches in adopting and implementing Islamic family law in their national legal systems.Indonesia is known for its dualistic legal system, where Islamic law is applied in the private sphere (religious courts) alongside the national legal system, which is rooted in colonial legal heritage. Brunei Darussalam, as an Islamic monarchy, applies Islamic law more comprehensively and consistently within its Sharia court system, particularly in matters of family and marriage.Tunisia has pursued family law reform with a modernist-secular approach that retains the values of maqāṣid al-syarī'ah as the basis for ethics and morality in legislation, without explicitly referring to classical fiqh.The method used in this study is a legal-normative method with a comparative approach, aiming to explore how each legal system formulates and interprets the obligation of maintenance between husband and wife.Tunisia has pursued family law reform with a modernist-secular approach that retains the values of maqāṣid al-syarī'ah as the basis for ethics and morality in legislation, without explicitly referring to classical fiqh. The method used in this study is a legal-normative method with a comparative approach, aiming to explore how each legal system formulates and interprets the obligation of maintenance between husband and wife.The research findings indicate that differences in maintenance provisions between husbands and wives in the three countries are significantly influenced by the fiqh school of thought adopted, the ideological orientation of the state, and local socio-political dynamics.